Charge Transfer Excitons and Possible Exitonic Pairing in the Extended Three Band Hubbard Model - Vermeulen, C; Barford, W; Gagliano, E (1995)
Exact diagonalisations of the extended Hubbard model are performed. In the insulating regime it is shown that the nearest neighbour copper-oxygen repulsion, $V$, leads to Frenkel excitons in the charge transfer gap at values of $V$ of the order of copper-oxygen hybridisation, $t$. In the metallic regime it is shown that the static charge-transfer and density-density correlation functions diverge as a function of $V$, indicating a charge-tansfer instability and phase separation. This is accompanied by a softening of the $q → 0$ mode of the dynamic correlation functions which is associated with the excitonic excitations responsible for the superconducting correlations observed in the proximity of the phase separation boundary of ref. \cite{cv95b}.